Robert D. Marcus, David Burner - Marcus, Robert D. (New York, 1995)
Part 1. Discovery and early settlement, Part 2. From colonies to republic, Part 3. The growth of a new nation, Part 4. Reform, slavery, civil war, and reconstruction.
Keywords: United States,Hoa Kỳ; History,Lịch sử